1982
DOI: 10.1111/j.1471-0528.1982.tb04703.x
|View full text |Cite
|
Sign up to set email alerts
|

Activity of serum cytidine deaminase during pregnancy

Abstract: Summary. A simple and reliable method for the estimation of cytidine deaminase (cytidine aminohydrolase; EC 3.5.4.5) activity in pregnancy serum is described. This enzyme does not require magnesium for activation and is also more stable than deoxycytidylate deaminase (dCMP deaminase, dCMP aminohydrolase; EC 3.5.4.12). There was excellent correlation between the two enzymes (r= 0.92). Both enzymes showed increased activity in abnormal pregnancy. Both enzyme activities were found to be similar in 1305 maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1983
1983
1994
1994

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 4 publications
0
15
0
Order By: Relevance
“…3.5.4.12) and had demonstrated elevated dCMP deaminase activity in patients with pre-eclampsia and other causes of high-risk pregnancies Jones, 1975,1982). CD is more stable than deoxycytidylate deaminase and Jones et al (1982) claimed that the discrimination between normal and high-risk pregnancies was as good when CD was measured as when dCMP deaminase was used. Baines and Clark (1985) also investigated the use of serum CD as a marker for pre-eclampsia using a similar method but with the ammonia determined after incubation of serum with substrate for only 2 h at 37 "C, using the glutamate dehydrogenase end-point method (1975).…”
Section: Cytidine Deaminasementioning
confidence: 98%
See 1 more Smart Citation
“…3.5.4.12) and had demonstrated elevated dCMP deaminase activity in patients with pre-eclampsia and other causes of high-risk pregnancies Jones, 1975,1982). CD is more stable than deoxycytidylate deaminase and Jones et al (1982) claimed that the discrimination between normal and high-risk pregnancies was as good when CD was measured as when dCMP deaminase was used. Baines and Clark (1985) also investigated the use of serum CD as a marker for pre-eclampsia using a similar method but with the ammonia determined after incubation of serum with substrate for only 2 h at 37 "C, using the glutamate dehydrogenase end-point method (1975).…”
Section: Cytidine Deaminasementioning
confidence: 98%
“…The early work on CD was carried out using the method first described by Jones et al (1982). This involved incubation of serum (100 pL) with deoxycytidine in carbonate/bicarbonate buffer (pH 9.2) for 18 h at 22 "C. The ammonia produced was estimated using the Berthelot reaction.…”
Section: Cytidine Deaminasementioning
confidence: 99%
“…It is therefore for this reason that a single serum was added to the Standards. A similar technique has been described by Jones et al (4).…”
Section: Influence Of Serum On the Berthelot Reactionmentioning
confidence: 99%
“…SF4-006FG5) was used for estimatifig the cat alytic activity concentration of serum lkaline phosphatase (37 °C). Cytidine deaminase (22 0 C) was assayed aecording to Jones et al (4).…”
Section: Other Enzyme Assaysmentioning
confidence: 99%
“…Measurement of the activity of CD in serum was proposed as a new method for the early detection of pre-eclamptic toxaemia, cholestasis of pregnancy and intra-uterine death (Jones et al, 1982). However, other investigators have reported a poor correlation of elevated CD activity with pre-eclampsia (Baines and Clark, 1985;Sherwood et a l , 1987).…”
Section: Introductionmentioning
confidence: 97%